SPECTRAL AND PHOTOMETRIC STUDY OF THE OBJECT IRAS20462 + 3416 - L.N. Kondratyeva; E.K. Denissyuk; I.V. Reva; M.A. Krugov (Academic Scientific Journal of Computer Science, 2019)
RAS20462 + 3416 belongs to low-mass post-AGB stars with a dense compact envelope, which was formed in the process of the mass loss by the star at the end of the pulsating AGB phase. The spectrum of the object consists of the HI, [NII], [SII] emission lines and of HeI, which is mainly observed in absorbtion. The temperature of the central star corresponds to the value Teff = 19500 ± 500К, the electron density is 104 cm-3. Several episodes of gas ejection from the atmosphere of the central star were recorded. So, in 1993 - 1994, PCygni profiles appeared in the UV and optical spectral lines. The stellar wind velocity was 800 - 990 km/s. The photometric variability of the object was noted by many authors. In particular, quasi-periodic oscillations of brightness in the optical range with an amplitude of 0.m1 - 0.m2 and a period of 4 days were detected. Rapid fluctuations in brightness can be caused by stellar pulsations and continuing mass loss. In this paper, we present new spectral and photometric data obtained mainly in 2015–2018. Irregular brightness variations were detected in B, V, and R filters with an amplitude of 0m.4. The results of spectral observations indicate a gradual increase in emission line fluxes. Thus, absolute fluxes in Hβ, Hα, [NII] lines increased by about 30 – 40%. In terms of its physical parameters and the nature of the spectrum, the object is similar to a young planetary nebula of low excitation. However, the irregular variability of brightness and fluxes in emission lines, as well as the observed episodes of the matter ejection, indicate that the shell formation has not finishhed. Most likely this object can be considered as a protoplanetary nebula.